Farm Funds Optimisation For Community Entrepreneurship At Tobati Village Jayapura City - Rante , Yohanis; Ratang, Sarlota (Advances in Social Sciences Research Journal, 2019)
The village fund is expected village government and technical institutions can realize the vision of Jayapura city government that believes, independent, unified, modern, prosperous based local wisdom. The city of Jayapura has established the Community Entrepreneurship Agency (BKM) in each village/village/Kelurahan in order to manage the funds of the village/village/Kelurahan more effectively, efficient, precisely targeted to support the governance activities Good and transparent. The purpose of this research is to describe the management of ADD in village community empowerment as well as driving and inhibiting factors. The results showed that optimizing village funds allocation in the development of community entrepreneurship at Village Tobati Jayapura City is already running but not maximally, hence the need for strategy. STRATEGY (W-O) makes strategy that utilizes the opportunity to overcome weaknesses, namely consist of: Government policy that makes Village Tobati as a demonstration village for tourism, this is an opportunity to add Income or family’s confidentiality. The help of Village fund, ADK, ADD the average routine each year. The commitment of the city government to improve and develop fisheries sector, especially the cultivation of fish cages very smooth and good means of transportation, and the help of the Prospect fund from the years 2016 and 2017 for the business of kiosk, sales Pinang, vegetable sales + Seasoning Kitchen, selling cold beverages + juice jacket, selling yellow rice, handicraft business, business selling pulse, oil kerosene + gasoline, net business. The opportunities mentioned above show that weaknesses in Village Tobati can be overcome well because of the very dominant opportunities in the village. Therefore the need for awareness from the local community to take advantage of the opportunities that exist for the welfare of the family in doing some very promising efforts.